Comparison of Hepcidin Levels in Children with and without Soil-Transmitted Helminths Infection - Dewi Saputri; Yunilda Andriyani; Almaycano Ginting (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Helminths infection is one of the diseases that still occur insociety. The helminth infection caused by the Soil-Transmitted Helminths (STHs) group, which is Ascaris lumbricoides, Trichuris trichiura, and hookworm in human can cause chronic bleeding resulting in decreasir on storage in the body and increased level of hepcidin. Hepcidin is a liver hormone which regulates iron metabolism and can function as marker of inflammation and iron deficiency. This study aimed to compare the hepcidin levels in STH-infected and non-infected children. A cross-sectional study was conducted betweenMay and October 2018 on 28 STH infected and 140 non-infected subjects. The collected stool samples were analyzed using the Kato-Katz method to determine the presence of STH infection and the degree of infection. Urine samples were processed, and their hepcidin levels were measured using a Sandwich-ELISA method. Measurement was made using a Spectrophotometer. The difference of numeric variables was analyzed using Wilcoxon test. The prevalence of STH infection was 16.66%. The prevalence of Trichuris trichiura 10.71%, Ascaris lumbricoides 4.76% and hookworm 2.97%. The prevalence of a single infection was 14.88% and mixed infection 1.78%. Based on the intensity of infection, 15.48% of subjects were mild infection, 0.59% moderate infection, and 0.59% severe infection. Hepcidin levels in the infected and uninfected group did not differ significantly (p=0.978). There were no different hepcidin levels in children with and without soil-transmitted helminths infection.